Detecting the occurrence of indigenous and non-indigenous megafauna through fishermen knowledge: A complementary tool to coastal and port surveys. (October 2019) - Azzurro, E.; Bolognini, L.; Dragičević, B.; Drakulović, D.; Dulčić, J.; Fanelli, E.; Grati, F.; Kolitari, J.; Lipej, L.; Magaletti, E.; Marković, O.; Matić-Skoko, S.; et al.
Abstract: Marine bioinvasions and other rapid biodiversity changes require today integrating existing monitoring tools with other complementary detection strategies to provide a more efficient management. Here we explored the efficacy of fishermen observations and traditional port surveys to effectively track the occurrence of both indigenous and non-indigenous megafauna in the Adriatic Sea. This consisted mainly of mobile taxa such as fishes, crustaceans and molluscs. Port surveys using traps and nets within 10 major Adriatic harbours, were compared with the information obtained from 153 interviews with local fishermen. Information gathered by traps and nets varied significantly and generally resulted of limited efficacy in exotic species detection. Interviews allowed tracking the occurrence of new species through time and space, providing complementary knowledge at the low cost. This combined approach improves our capability of being informed on the arrival of species of different origin, providing a more rational, improved basis for environmental management and decision making. Graphical abstract: Image 3 Highlights: Traditional port surveys resulted in a wide number of recorded taxa but few NIS. Fishermen reported information on a wide number of NIS, mostly collected by nets. Fishermen knowledge aid completing the baseline information in a port region.